Modelling of Crack Propagation in Layered Structures Using Extended Finite Element Method - Nasaj Moghaddam, Hesamoddin; Keyhani, Ali; Aghayan, Iman (Salehan Institute of Higher Education, 2016)
Crack propagation in structures is an important issue which is engineers and designers should consider. Modeling crack propagation in structures and study the behavior of this phenomenon can give a better insight to engineers and designers for selecting the construction’s materials. Extended finite element method (XFEM) was used successfully in the past few years for simulating crack initiation and propagation in sophisticated and complex geometries in elastic fracture mechanics. In this paper, crack propagation in three-point bending beam including initial crack was modeled based on ABAQUS software. The following consequences were attained through the study of simulation data. First, the effects of young’s modulus and fracture energy on force-displacement curve at three-point bending beam were investigated. It was observed that, by increasing the value of young’s modulus and fracture energy, three-point bending beam was showed more load carrying against initiation. Second, in multi-layer beam, the effect of young’s modulus on force-displacement curve was investigated. In case I (the thin upper layer is harder than the substrate) the value of young’s modulus in substrate was kept constant and the amount of young’s modulus in thin layer was risen in each step rather than the substrate, the peak in force-displacement curve was ascended and three-point bending beam resisted better against crack initiation. Next, similar conditions was considered in case II (the thin upper layer is softer than the substrate), by decreasing the value of young’ modulus in top layer, peak in force-displacement curve was declined and crack initiation was happened in lower loading in each step. Finally, sensitivity analysis for thickness of top layer was conducted and the impact of this parameter was studied.